Molecular Characterization of Salmonella Isolates of Duck in Comparison to Salmonella Isolates of Chicken and Ruminants (Bangladesh Journal of Microbiology, 2010)
Salmonella species are recognized as a major cause of food borne illness that are closely associated with the consumption of contaminated poultry and egg products. The present study was conducted to compare the cultural, biochemical characteristics, antibiotic sensitivity pattern and the patterns of genomic organization of duck Salmonella isolates associated with chicken, cattle, sheep and goat using pulsed-field gel electrophoresis (PFGE) with Xba1 restriction enzyme. The comparative antibiogram study among duck, chicken and ruminants showed variable results in antibiotic sensitivity and similar results in resistance pattern. Genome analysis using PFGE with Xba1 restriction enzyme revealed that the Salmonella isolates of the same species collected from same areas to be of same genomic pattern, although a great genomic diversity could be found among duck, chicken, sheep, goat and cattle Salmonella strains. It may be concluded from the result of this research work that the heterogeneity in genomic organization among different isolates of different species collected from different areas occurred greatly and for this reason. Keywords: Salmonellosis; Salmonella; Pulsed-field gel electrophoresis (PFGE); Duck; Chicken; RuminantsDOI: http://dx.doi.org/10.3329/bjm.v25i2.4868 Bangladesh J Microbiol, Volume 25, Number 2, December 2008, pp 91-94